The significance of cephalopod beaks as a research tool: An update - Xavier, José C.; Golikov, Alexey V.; Queirós, José P.; Perales-Raya, Catalina; Rosas-Luis, Rigoberto; Abreu, José; Bello, Giambattista; Bustamante, Paco; Capaz, Juan C.; Dimkovikj, Valerie H.; González, Angel F.; Guímaro, Hugo; et al. (Frontiers in Physiology, 2022)
The use of cephalopod beaks in ecological and population dynamics studies has allowed major advances of our knowledge of the role of cephalopods in marine ecosystems in the last 60 years. Since the 1960´s, with the pioneering research by Malcolm Clarke and colleagues, cephalopod beaks (also named jaws or mandibles) have been described to species level and their measurements have been shown to be related to cephalopod body size and mass, which permitted important information to be obtained on numerous biological and ecological aspects of cephalopods in marine ecosystems. In the last decade, a range of new techniques has been applied to cephalopod beaks, permitting new kinds of insight into cephalopod biology and ecology. The workshop on cephalopod beaks of the CIAC Conference (Sesimbra, Portugal) in 2022 aimed to review the most recent scientific developments in this field and to identify future challenges, particularly in relation to taxonomy, age, growth, chemical composition (i.e. DNA, proteomics, stable isotopes, trace elements) and physical (i.e. structural) analyses. In terms of taxonomy, new techniques (e.g. 3D geometric morphometrics) for identifying cephalopods from their beaks are being developed with promising results, although the need for experts and reference collections (of cephalopod beaks) will continue. The use of beak microstructure for age and growth studies has been validated. Stable isotope analyses on beaks have proven to be an excellent technique to get valuable information on the ecology of cephalopods (namely habitat and trophic position). Trace element analyses is also possible using beaks, where concentrations are significantly lower than in other tissues (e.g. muscle, digestive gland, gills). Extracting DNA from beaks was only possible in one study so far. Protein analyses can also be made using cephalopod beaks. Future challenges in research using cephalopod beaks are also discussed.